Studi Fenomenologi : Pengabaian Gejala Awal Kanker mengakibatkan Respon Negatif bagi Klien dan Keluarga - Kristianto Dwi Nugroho (Jurnal Keperawatan Malang, 2020)
Background: Cancer is a growth of a cell different that another cell, and can attack other tissues and organs. Cancers must begin with relatively mild initial symptoms. But many patients who ignore the early symptoms of cancer that appear, to the symptoms of cancer with severe advanced stage. This neglect usually has a negative impact on both the patient and family. Purpose: The purpose of this study is to analyze the experience of patients with cancer from the beginning to the client experiencing further treatment. Method: This research is a qualitative study with a phenomenological approach. Results: In this study found two main themes: 1) Ignoring the initial symptoms so that cancer treatment is done; 2) Negative responses from clients and families due to cancer. Conclusion: There is a need for education to outside communities about the early symptoms of cancer, so that people are more aware and immediately check the situation. Negative responses that arise can worsen the healing process, so it is necessary to stress management for clients with cancer.